Leucocyte Value as a Signs of Microvascular Inflammation in Type 2 Diabetes Mellitus Patients - Amelia, Ria; Aulia, Fadila; Luhulima, Danny (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Problems in the pathogenesis of Type 2 Diabetes Mellitus (T2DM) to complications are often overlooked, and routine blood tests are rarely performed in individuals with T2DM. Inflammation is an important early sign for detecting complications. One of the factors that can be used as an indicator of inflammation is the value of leukocytes. The purpose of this study was to assess leukocyte counts in patients with T2DM as a sign of inflammation in T2DM patients. This study used a cross-sectional approach method, with data analyzed descriptively and correlative using SPSS software. The subjects of the study involved residents assisted by the Kota Baru and Kalibaru Health Centers who suffered from DMT2 in the period from January to February 2019. The results of the Pearson test showed a value of p = 0.49, which indicated that there was no significant relationship between leucocytosis and blood glucose levels. The conclusion of this study is that the high number of leukocytes in T2DM patients is thought not to be caused by high blood glucose levels, but may be influenced by other factors related to the development of complications of T2DM disease. This research has important implications in understanding the pathogenesis and prevention of complications of T2DM.